Effects of Methods and Time of Pollination on Tomato (Lycopersicon esculentum) Fruit Set and Seed Quality - C. MANJUNATHA,; B.S. TOMAR,; BALRAJ SINGH,; KALYANRAO, (Seed Research, 2026)
An investigation was carried out to study the effects of method and time of pollination on fruit set, seed yield, 100-seed weight and germination in tomato (Lycopersicon esculentum) cv. Pusa Divya, developed through functional male sterility, under open field and polyhouse conditions. The repeated (twice) pollination of the same stigma resulted in significantly higher fruit set and seed yield than those pollinated once (without emasculation). Pollinations at 9.00 AM and 5.00 PM were better for higher fruit set and seed yield.